Right to legal representation of children in conflict with the law - International and regional standards - Netkova, Bistra N.A; Qosaj Mustafa, Ariana Qosaj (Advances in Social Sciences Research Journal, 2017)
Legal aid/legal representation is an essential element of a fair, humane and efficient criminal justice system that is based on the rule of law. The right to legal representation is a precondition of children’s access to justice. Children left alone without any independent legal counsel are not only deprived of their voice, but are also subject to numerous abuses as they are often intimidated and not aware of their rights, although these are guaranteed by almost all of the countries in the world. The right to legal representation of children in conflict with the law is proscribed by the ICCPR, the ECHR, and specifically regarding children only the UN Convention on the Rights of the Child (CRC). However, even though these international instruments provide a consistent of standards on child‐friendly measures for the provision of legal assistance to children, they do so in a very general manner. Only the Council of Europe Guidelines on Child‐Friendly Justice, gives specific guidance on how lawyers, paralegals, should interact with child clients and their families, with child and other victims, with the police and prosecuting agencies, or with courts or tribunals designated to adjudicate cases. Therefore, there is much space for future development of possible international legal document that will address this issue in more specific manner.